Population structure of two freshwater amphipods (Crustacea: Peracarida: Hyalellidae) from southern Brazil - Ozga,Aline Vasum (2018)
Abstract Two recently described amphipods species from southern Brazil, Hyalella georginae Streck and Castiglioni, 2017 and Hyalella gauchensis Streck and Castiglioni, 2017, had their population structures characterized by sex, females’ ovigerous condition, cephalothorax length (mm), size-class frequency distribution, sex-ratio, reproductive period, and recruitment. The specimens were collected with a dip net from a stream source (H. georginae) and from a water reservoir (H. gauchensis) in the Palmeira das Missões municipality, state of Rio Grande do Sul, Brazil, from August 2012 to July 2013 (12 months). Both species showed a bimodal frequency distribution for total and seasonal size classes, with males larger than females. Overall, the sex ratio favored females when analyzed monthly and seasonally. Ovigerous females were recorded throughout the year, with higher frequency in spring (H. georginae) and summer (H. gauchensis), characterizing a seasonal reproduction. Both species showed continuous recruitment, with greater intensity in the spring. The population structure of these two Hyalella species had similar features, showing continuous recruitment and seasonal reproduction related to their life-history strategies, which promote adaptations to their habitat.